Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

PLEASE DON'T SKIP

Solve the system of equations.



PLEASE DONT SKIP Solve The System Of Equations class=

Sagot :

AL2006

                2x + 3y = 1

                y = 3x + 15

There's not much you can do with the first equation, because it has
two variables in it ... 'x'  and  'y' .  No matter how much you move them
around, you'll never be able to get either one equal to just a number. 
Is there any way you could get rid of one of the variables in the first
equation, and have just 1 letter in it to solve for ?

Absolutely !  The second equation tells you something that 'y' is equal to,
(3x + 15).  "EQUAL" is very powerful.  It means that wherever you see 'y',
you can put (3x + 15) in its place, and you won't change anything or
upset anything.  One thing you can do is take that (3x + 15) from the
2nd
equation, and put it right into the first equation in place of 'y'. 
You'll see how that helps as soon as you do it.

             First equation:    2x + 3y = 1

         Substitute for 'y' :    2x + 3(3x + 15) = 1

 Remove parentheses:    2x + 3(3x) + 3(15) = 1
                                        2x +  9x    +    45  =  1

Combine the terms with 'x' in them:    11x + 45 = 1

Look what you have now !  An equation with only one variable in it !

Subtract  45  from each side:    11x = -44

Divide each side by  11 :            x = -4

You're more than halfway there.  Now you know what 'x' is,
and you can use it with either equation to find what 'y' is.

-- If you use it with the first equation:      2x + 3y = 1

       Put in the value of 'x':    2(-4) + 3y = 1

Remove the parentheses:      -8 + 3y = 1

        Add  8  to each side:              3y = 9

    Divide each side by  3 :               y = 3


-- If you use it with the 2nd equation:    y = 3x + 15
 
            Put in the value of  'x' :      y = 3(-4) + 15

       Remove the parentheses:      y = -12 + 15

Add numbers on the right side:     y = 3  (same as the other way)

So there's your solution for the system of two equations:

         x = -4
         y = 3


We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.